Challenges of Drilling and Loading 30 and 48 Inch Poduction Blast Holes in a Unique Oilsands Environment - David P. Reddick (International Society of Explosives Engineers, 1992)
"Suncor Inc. Oilsands Group mining operation in Northern Alberta, Canada, has been blasting to loosen the oilsands to increase production and decrease maintenance of the bucketwheel excavators for over twenty years. In 1991 an area of the mine was encountered which had a working face of 130 feet rather than the usual 20 to 57. In order to maintain production objectives, the planning and blasting departments of the mine took on the task of blasting as much of the working face as possible. McGinnis Rathole Drilling Company provided the drilling for the project and Mining Services International (MSI) delivered the bulk explosives to the boreholes. It is believed the resultingblasts exceeded several known records in production blasting."